Application of LC-MS/MS methods in the quantification of oxidative stress parameters - Crevar, Milkica; Guzonjić, Azra; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
Oxidative stress is a phenomenon that occurs due to the disturbance in the balance between the production of reactive oxygen species and the ability of biological systems to remove the resulting compounds. Oxidative stress is involved in the pathogenesis of many disorders in the human organism. This indicates the importance of quantification of oxidative stress parameters in biological samples. Traditionally, these parameters are determined by biochemical tests. Although these tests are routinely performed, they have many drawbacks. To determine the exact concentration of selected compounds, more sensitive analytical methods are becoming more important. In the modern scientific literature, liquid chromatography-tandem mass spectrometry (LC-MS/MS) is increasingly mentioned. This method, with adequate selection of stationary and mobile phases, enables quantification of very low concentrations of selected parameters. In addition, these methods can simultaneously determine the concentration of many selected components. However, it is necessary to take into account that LC-MS/MS methods require a very purified biological sample from which the proteins have been maximally removed. In this work, we will present the results of determination of cysteine, cystine, reduced and oxidized glutathione in patients with microcellular lung cancer. The use of LC-MS/MS methods is becoming increasingly common for the analysis of oxidative stress markers in biological fluids. In the future, we are expected to move to even more modern, fully automated methods, which simultaneously purify and analyze samples.